Environmental law in Malaysia: an overview / Zulfakri Mohd. Din - Mohd. Din, Zulfakri (Faculty of Law, 1987)
Every individual is a part of the environment, and his actions and reactions are a result of that individual's perception. Environment is everything that surrounds, that to an individual is the world that makes an individual and his world unique. It is a private environment, the acceptance of which by any individual would vary according to how that individual allows the environment to affect him. To say that man has never realised that the intimate relation— ship between himself and his natural surroundings would be erroneous because man is a part of nature. Islam teaches that nature is creation and gift. As creation it is teleological, perfect and orderly. As a gift it is an innocent good placed at the disposal of man. Islam also teaches that value was created as a "field" for man to grow and prosper, to enjoy God's bounty and in doing so, prove oneself ethically worthy. Nature is not man's property but God's. Man only has a tenure which is granted by God for the end prescribed by Him. Just as any responsible tenant, man ought to take care of his master's property. Islam further teaches man to search for and understand the general order and beauty of nature, and not merely to view her from the point of natural sciences. Sensitivity to nature and tender care given to her as garden or forest, river or mountain, is attunement with the divine purpose.